(untitled) (The Pakistan Development Review, 1994)
Technology in the nineteenth century was designed according to the prevailing resource endowment and was labour intensive as industrialised countries in the 19th century invented their own technology as their resource endowment demanded -capital had to be found from personal savings of the investors-which acted as a check on development of technologies making high demand on capital. In such an economic environment there was a direct and positive linkage between output and employment. Employment being thus a linear function of output, the employment optimisation path coincided with the output optimisation path. Not so now. The latecomers in the industrial field in the twentieth century have to select from the available capital-intensive technologies designed for a labour saving mode of production. A conflict between output and employment thus arose because of (1) the labour-intensive technologies higher capital input and higher price per unit of output arising out of the limited scale of production, as against the capital-intensive technologies, lower capital input and lower price per unit of output arising out of larger scale of economy. The resulting trade-off between output and employment involves a more complex question of the weightage to be given to current as against future output compared with the weightage to be given to current as against future employment. Optimum welfare would therefore result from maximising current output and employment by maximising the present value of the entire streams of output and employment over time.